The evaluation of facilities and infrastructure standards achievement of vocational high school in the Special Region of Yogyakarta - Sugiyono Sugiyono (Graduate School, Universitas Negeri Yogyakarta, 2021)
The objectives of the study are to determine (1) the achievement of standard facilities and infrastructure for vocational high school in the Special Region of Yogyakarta, (2) the supporting factors for achieving the standard of facilities and infrastructure, and (3) the inhibiting factors for achieving the standard of facilities and infrastructure. This study employed an evaluation research method with a survey approach. The research sample was six vocational high schools in the Special Region of Yogyakarta, which was chosen through purposive sampling, taking into Cluster 1, Cluster 2, and Cluster 3. Data collection techniques used were Focused Group Discussion techniques, questionnaires, documents, observations, and interviews. The validity of the questionnaire instrument used expert validation. Analysis of quantitative data was conducted through descriptive analysis techniques and qualitative data with interactive analysis models. The results of the study show that (1) the standard of facilities shows that the average school data has met facilities and infrastructure standards, (2) the supporting factors for achieving the standard of facilities and infrastructure are (a) the principal's policy in developing facilities and infrastructure, (b) government support through programs to develop and achieve national education standards, (c) community support through school committees, (d) education board support, and (3) the inhibiting factors for achieving facilities and infrastructure standard are: (a) the lack of teacher media innovation developed in vocational high school; (b) the lack of maximization and maintenance of infrastructure in vocational high school; (c) the lack of support in classrooms and workshops, especially in the connectivity aspect.